The development of Differentiation Intelligent Tutoring System (DifITS): example-tracing tutor approach / Felix Sing Tiing Chuo, Mohammad Nur Azhar Mazlan and Kian Sam Hong - Sing, Tiing Chuo; Mazlan, Mohammad Nur Azhar; Kian, Sam Hong (UiTM Press, 2016)
Calculus is an important branch of Mathematics for post-secondary education in various disciplines. Students are introduced to Calculus through the topic of Differentiation when they are in secondary school. However, the analyses of the Additional Mathematics’ answer scripts of the Sijil Pelajaran Malaysia (SPM) (Malaysian Certificate of Education equivalent to GCE O’ Level) examination, has shown that students are not doing well in this topic. Past empirical studies done locally and overseas have also shown that many undergraduates face difficulties in learning Calculus, thus hindering their undergraduate studies. Therefore, there is a need to address this learning deficit, and with increasing class sizes in school and tertiary institutions, a technology-enabled solution with minimal human intervention, the Differentiation Intelligent Tutoring System (DifITS), as proposed by this study, could be a viable approach to assist students’ learning for this subject. DifITS is promoted as a web-based tutor, using the Example-tracing tutor approach to provide one-to-one tutoring and self- paced learning for the students. The Example-tracing tutor will be applied using Cognitive Tutor Authoring Tools (CTAT). A behavioral graph will be created to track students’ answers in order to provide hints and feedback. In addition to enhanced learning, it is anticipated that DifITS will motivate students as the tutoring mechanism involves animation to enable students to visualize the procedural process of Differentiation. In addition, DifITS will also focus on conceptual understanding through graphs to show the rate of change and motion for the respective differentiation procedures.